ANALISA PENYIMPANGAN IKLIM DARI FENOMENA ENSO MENGGUNAKAN MODEL KORELASI STUDI KASUS BOGOR - Annisa Luthfianti Panular; Rahmat Gernowo (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Cases of climate anomalous in Indonesia, many have influences on the climate in several areas such as the dry or rainy season that does not occur periodically or the precipitation decrease that does not normal and deviated from ought. This study aimed to analyze the climate anomalous and correlation patterns of ENSO towards rainfall variability in Darmaga Bogor, then compared the results with rainfall of Tanjung Priok Jakarta. Both places have minimum ENSO influence because they being away from the center of ENSO events that is in the Pacific Ocean and located in the west Pacific. Climate anomalous due to ENSO (El Niño Southern Oscillation) in the Indonesian archipelago can occur if in the Pacific El Niño is more decreasing rainfalls or La Niña which further adds to the amount of rainfall.This research using a linear correlation analysis model and contour of the sea surface temperature (SST) from GrADS software. The data used are Index Nino 3.4 anomaly, IOD (Indian Ocean Dipole) anomaly, precipitation and SST anomaly data. Data is processed from January 2004 - December 2013 (10 years). Correlation of index Nino 3.4 years 2004-2013 showed a lot more going to negative index that means more towards the La Niña in Pacific Ocean. The results of correlation analysis in August in Darmaga between ENSO - IOD with rainfall that more affects the rainfall pattern is a ENSO factor either La Niña nor El Niño and also it followed by west monsoon wind pattern, whereas at Tanjung Priok that more affects the rainfall pattern is monsoonal rainfall patterns. Upon the precipitation in Darmaga generally has high enough intensity and some graph pattern follows monsoonal rainfall patterns whereas Tanjung Priok generally has low intensity and the graph pattern follows the type of monsoonal rainfall patterns. SST contour in West Java is on average warmed up that caused that region more easily condensed the clouds and atmospheric pressure at the waters becomes high.